Molecular Detection of Hymenolepis Nana from Patients in Al-Shatrah Hospital - Al-Ataby, Fatimah. H.; Hadi, Wala, a Hasan; Radhi, Lamyaa .Y. (American Journal of Biology and Natural Sciences, 2025)
This study was carried out at in Thi-Qar Province, College of Science Department of Pathological analysis .The samples were collected from Patients in Al-Shatrah hospital 65 Samples was collected from patients suffering from diarrhea and abdominal pain in different age from male and female . The sample were collected in a clean plastic containers and labeled it with writing the number, age and sex and then transported in refrigerated bag than kept cool until the sample exanimated. Microscopically examination include and also used molecular detection by DNA extraction and PCR amplification. The result was positive for only 37 sample show Hymenolepis nana in all methods that used.